2017
DOI: 10.15537/smj.2017.2.16320
|View full text |Cite
|
Sign up to set email alerts
|

The association between body mass index and academic performance

Abstract: Objectives:To examine the relation between body mass index (BMI) and the academic performance of students from Taif city, Kingdom of Saudi Arabia (KSA) using the grade point average (GPA).Method:A cross-sectional study that includes students from intermediate and high schools located in Taif city, KSA between April 2014 and June 2015. Height and weight were measured and BMI calculated. Related risk factors including dietary habits, activity, parent’s education, sleeping pattern, and smoking were recorded.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 13 publications
8
22
2
1
Order By: Relevance
“…Our previous findings of studies carried out in Chile and those from other countries did not find any associations between the current nutritional status (according to Z-BMI) and SA; these results confirmed that Z-BMI is not suitable to explain SA [37,38,39,40,41,42,43,44,45,46]. …”
Section: Discussionsupporting
confidence: 62%
“…Our previous findings of studies carried out in Chile and those from other countries did not find any associations between the current nutritional status (according to Z-BMI) and SA; these results confirmed that Z-BMI is not suitable to explain SA [37,38,39,40,41,42,43,44,45,46]. …”
Section: Discussionsupporting
confidence: 62%
“…But had better percentage in class attendance than the overweight participants (Table 8). This finding is similar 16 to the finding of Alswat KA et al showing no correlation between the BMI and academic performance.…”
Section: Discussionsupporting
confidence: 92%
“…It was conducted between April 2014 and June 2015 [15]. The research proposal was approved by the ethical committee at Taif University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%